Distribution of Beta-Lactamase Producing Gram-Negative Bacterial Isolates in Isabela River of Santo Domingo, Dominican Republic - Calderón, Víctor V.; Bonnelly, Roberto; Del Rosario, Camila; Duarte, Albert; Baraúna, Rafael; Ramos, Rommel T.; Perdomo, Omar P.; Rodriguez de Francisco, Luis E.; Franco, Edian F. (Frontiers in Microbiology, 2021)
Bacteria carrying antibiotic resistance genes (ARGs) are naturally prevalent in lotic ecosystems such as rivers. Their ability to spread in anthropogenic waterscould lead to the emergence of multidrug-resistant bacteria of clinical importance.For this study, three regions of the Isabela river, an important urban river in the city of Santo Domingo, were evaluated for the presence of antibiotic resistance genes. The Isabela river is surrounded by communities that do not have access to proper sewage systems; furthermore, water from this river is consumed daily9for many activities, including recreation and sanitation. To assess the state of10antibiotic resistance dissemination in the Isabela river, nine samples were collected from these three bluedistinct sites in June 2019 and isolates obtained from these sites were selected based on resistance to beta-lactams. Physico-chemical and13microbiological parameters were in accordance with the Dominican legislation. MALDI-TOF mass-spectrometry analyses of ribosomal protein composition re-vealed a total of 8 different genera. Most common genera were:Acinetobacter16(44.6%) andEscherichia(18%). Twenty clinically important bacterial isolates were dentified from urban regions of the river, these belonged to generaEscherichia18(n= 9),Acinetobacter(n= 8),Enterobacter(n= 2) andKlebsiella(n= 1). Clinically important multi-resistant isolates were not obtained from rural areas. Fifteen isolates were selected for genome sequencing and analysis. Most isolates were resistant to at least three different families of antibiotics. Among beta-lactamase genes encountered, we found the presence of blaTEM, blaOXA, blaSHVand blaKPC through both: deep sequencing and PCR amplification. Bacteria found from genus KlebsiellaandEnterobacterdemonstrated ample repertoire of antibiotic resistance genes, including resistance a family of last resort antibiotics reserved for dire26infections: carbapenems. Some of the alleles found were KPC-3, OXA-1, OXA-72,27OXA-132, CTX-M-55, CTX-M-15 and TEM-1